The Effect of Back Massage on Reducing Back Pain in Third-Trimester Pregnant Women at Adow Community Health Center - Ancella Impe; Sulistiyah Sulistiyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2026)
Background: Discomfort in third trimester pregnant women often arises due to physiological changes, with back pain being the most common complaint, occurring in 70% to 90% of cases. If left untreated, this pain can interfere with daily activities, cause insomnia, and even affect the childbirth process. Objective: This study aimed to determine the effect of back massage on reducing the intensity of back pain in third trimester pregnant women at Adow Community Health Center. Methods: The research design used a pre experimental approach with a one group pretest posttest design. The sample consisted of 40 third trimester pregnant women experiencing back pain at Adow Community Health Center. Data were analyzed using the paired t test statistical method. Results: Before receiving back massage, the majority of respondents (57.5%) experienced moderate scale pain. After the intervention, the majority of respondents (70%) reported a reduction in pain to a mild scale. The statistical test results showed a p value of 0.000 (p < 0.05) with an average pain reduction of 1.125. Conclusion: Back massage has a significant effect on reducing the intensity of back pain in third trimester pregnant women at Adow Community Health Center.